The manifestations of the Positivist Current in Scientific Education (Research, Society and Development, 2021)
Science has many traces of philosophical currents that existed in the history of humanity, among them positivism. This current originated in the Enlightenment has striking characteristics where science is considered an absolute truth, however its dynamism is known. The objective of this work was to highlight these manifestations in science education at a basic education school in Quixelô, Ceará. For that, questionnaires were applied to elementary school students for data collection. It was evidenced that in the school there are positivist currents concerning scientific education, this can be evidenced because the students believe that science is an absolute truth, so that it presents concrete and immutable answers. Thus, we realize that the positivist current is present in basic education, and it is necessary for teachers to explain how science is in constant resignification.